Conceptualizing Lifestyle and Routine Activities in the Early 21st Century: A Systematic Review of Self-Report Measures in Studies on Direct-Contact Offenses in Young Populations - Engström, Alexander (Crime & delinquency, 2021)
Criticism is commonly directed at research based on lifestyle-exposure theory and routine activity theory for the use of imprecise measures. To examine this issue further, this systematic review maps activities used as indicators of lifestyle and routine activities in studies on direct-contact crime among young individuals (mean age of 24 or younger). The results indicate that a broad range of activities are used as measures of lifestyle and routine activities in the 101 included studies. Studies on victimization often use illegal activities and substance use as measures of lifestyle or routine activities while studies on offending mainly rely on measures of unstructured and peer-oriented leisure activities. Overall, most studies seem more concerned with specific activities rather than routines or lifestyles.